The Role Of Economics In The Use Of Human Resources In The World Of Education - Saputra, Rifky Ardhana Kisno; Rohmah, Awawin Mustana (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The economy in Indonesia is currently in an unstable state, but the need for education is getting wider, the number of universities makes the competition for education even tighter. One of the provinces in Indonesia that has many universities is East Java. Over Over time, the number of new private universities has resulted in increasingly fierce competition to be able to meet the needs of private universities. On the other hand, if the old campuses that have been established for a long time do not innovate, they will be eliminated by the new campus. However, the number of private universities in East Java, out of 321 private universities, there are only 11 universities that are superior, this is a big record for the province of East Java, because the number of campuses that are established, has not been able to show superior quality for these private universities. One of the underlying factors that the private sector is good is human resources (HR) in this case lecturers. Lecturers are the most important urgency in accreditation, because good human resources will support good performance. As well as Lecturer Education, Lecturer Expertise, and Functional Positions. This study aims to determine the Role of Economics on Innovative Work Behavior (IWB) which is influenced by Creative Self – Efficacy (CSE) and Intrinsic Motivation (IM) in Permanent Lecturers of Private Universities in Lamongan Regency. The data analysis method uses structure equation modelling with AMOS software. Before the analysis with SEM, the model and data were tested with statistics (Classical Assumption Test, Validity Test, Reliability Test, Hypothesis Test). The result of this study is that the role of economics has a significant effect on Innovative Work Behavior.